STUDI PERBANDINGAN UJI MATERIAL ALUMINIUM MURNI (Al) DAN PELAPISAN ALUMINIUM MURNI DENGAN PERAK (Ag) MENGGUNAKAN METODA ELEKTROPLATING - Rosyid Ridlo Al Hakim; Aming Sungkowo (LPPM Poltek ST Paul, 2021)
Electroplating is the process of coating metal surfaces by electrochemical methods. The electroplating research process uses aluminum material, where aluminum is a material that is easy to obtain, lighter and cheaper than other metals. The purpose of this study was to determine the ability of the electric current to power aluminum (Al) coated with silver (Ag) by the electroplating method, to determine the effect of the magnitude of the electric current and the length of time the coating process took on the weight of aluminum coated with silver (Ag) and to determine the strength of the metal. aluminum after being tested using the Brinnell test. The method used is to compare pure aluminum (Al) and aluminum coated with silver (Ag) by electroplating at different currents so that it can determine the effect of the electroplating process. After that, the Brinnell test was carried out to determine the hardness of the aluminum (Al) material after electroplating was carried out. The results of the study are the amount of current that flows during the electroplating process is directly proportional to the thickness of the electroplating layer attached to the aluminum (Al) surface. If the electroplating process uses a large current, the results of the attached layer will look rough and not smooth, the electroplating layer also affects the material testing using the Brinnell method. The results of the Brinnell test prove that the hardness value of the aluminum (Al) material is directly proportional to the thickness of the layer.